(Invited) 4H-SiC Ion Implanted Bipolar Junctions: Relevance of the 1950°C Temperature for Post Implantation Annealing. (23rd August 2016) - Nipoti, Roberta; Parisini, Antonella; Sozzi, Giovanna; Puzzanghera, Maurizio; Parisini, Andrea; Carnera, Alberto
Abstract : In case of Al + implanted 4H-SiC, a post implantation annealing temperature of 1950°C has the beneficial effect of maximizing both the electrical activation of implanted Al and the reordering of the lattice damaged by the Al ions. However, the formation of extended defect in the implanted layers and that of carbon vacancies in the n-type epi-layers below the implanted layers may be hardly avoided. This study contains the results of structural and electrical investigation showing that: (i) on increasing the implanted Al concentration different type of extended defects form and grow; (ii) a strong anisotropic hole transport occurs when the Al implanted surface layer is confined by and contains stacking faults. This study contains also a study about the area and the perimeter current densities of Al + implanted 4H-SiC p-i-n diodes showing that: (iii) the sole hypothesis of carrier lifetimes dominated by carbon-vacancy related traps and the presence of a negative fixed charge at the sample surface allow us a good but not perfect simulation of the measured area and perimeter current components.